Exploring the Nexus between Moderate-to-Vigorous Physical Activity, Self-Disclosure, Social Anxiety, and Adolescent Social Avoidance: Insights from a Cross-Sectional Study in Central China - Shuyin Chen; Longjun Jing; Chuchu Li; Huilin Wang (MDPI AG, 2023)
Objectives: Psychological issues among adolescents represent a prevalent challenge in today's society. The purpose of this study is to explore the associations among moderate-to-vigorous physical activity, self-disclosure, social anxiety, and social avoidance in adolescents. Methods: This study collected cross-sectional data from 427 students in eight provincial key junior and senior high schools in the central China region of three provinces using snowball sampling and convenience sampling from July to August 2023. A structural equation model was employed to investigate the relationship between moderate-to-vigorous physical activity and social avoidance among adolescents. Results: The findings indicate that moderate-to-vigorous physical activity is negatively correlated with social anxiety (standardized coefficient = −0.219, p < 0.001) and positively correlated with self-disclosure (standardized coefficient = 0.454, p < 0.001). Social anxiety is negatively correlated with self-disclosure (standardized coefficient = −0.220, p < 0.001). Social avoidance is positively correlated with social anxiety (standardized coefficient = 0.461, p < 0.001) and negatively correlated with self-disclosure (standardized coefficient = −0.331, p < 0.001). Conclusions: The chain-mediated dual-path model between moderate-to-vigorous physical activity and social avoidance is facilitated by social anxiety and self-disclosure. In other words, adolescents who engage in more moderate to high-intensity physical activities exhibit lower levels of social anxiety, and those who have a stronger inclination for self-disclosure tend to demonstrate lower levels of social avoidance. In light of these findings, it is recommended that the government, society, schools, and families collaborate synergistically to promote the holistic well-being of adolescents and advance the development of a healthier China.